Feasibility and safety of percutaneous nephrolithotomy in the management of renal stones with emphysematous pyelonephritis following control of infection - Anshuman Singh; Surag K.R.; Anupam Choudhary; Suraj Jayadeva Reddy; Kasi Viswanath Gali; Abhijit Shah (Current Urology)
Abstract. Background. Management of renal calculi in the presence of emphysematous pyelonephritis (EPN) is challenging. The optimal management strategy for patients with EPN and renal calculi remains unclear. This study aimed to evaluate the safety and efficacy of percutaneous nephrolithotomy (PCNL) in the management of these patients and to provide insights into the postoperative outcomes and complications of PCNL according to the modified Clavien-Dindo classification. Materials and methods. This retrospective study included patients with EPN and renal stones who underwent PCNL, after initial conservative management, between January 2012 and December 2021. Patient demographics, presenting symptoms, features of septicemia, preoperative drainage, postoperative complications, and outcomes were recorded. Postoperative complications were categorized according to the modified Clavien-Dindo classification. Results. A total of 48 patients with EPN and renal calculi were included in this study. Percutaneous nephrolithotomy was performed 4–6 weeks later after obtaining a negative urine culture or under appropriate antibiotic coverage if the culture was unsterile. Of the total, 39 (81.25%) patients had postoperative complications, but only 9 (18.75%) patients had grade III or higher complications. Of these, 3 (6.25%) patients had grade IIIa complications, 3 (6.25%) had grade IIIb complications, 2 (4.1%) had grade IVa complications, and 1 (2.08%) had grade IVb complications and was admitted to the intensive care. No mortality was observed during the postoperative period. Conclusions. Initial conservative management of EPN followed by PCNL after initial infection control is an effective strategy for managing these patients. Patients with higher EPN grades have a higher risk of major postoperative complications after PCNL for renal stones. Specifically, patients with an EPN class 3 or 4 had a higher risk of complications than those with an EPN class 2 or lower. Patients with EPN class 1 have a relatively uncomplicated postoperative course after PCNL.